The biodiversity of lichens and their biomedical potential - Zhumaniyazova, A.Zh.; Bukabayeva, Zh.T.; Silybayeva, B.M. (Eurasian Journal of Applied Biotechnology, 2025)
Lichens are among the lower plants that are widely distributed on earth. In the science of lichenology, many scientific papers have been published by domestic and foreign scientists related to the species composition, structure, ecological significance, bioindicative properties of lichens and their areas of application [1-7]. The research work is based on the species, ecology and biological features of lichens distributed in various biomes of the Abay region. The study of 25 species of lichen distributed in the forests of pine (Pinus sulvestris L.) of Semey and the eastern part of small Kazakh mountains was carried out using different methods. The work on the identification of the studied species was carried out using a raster electron microscope. The collected 25 henna species were combined into 12 genera in 9 family. Depending on the ecology, epiphytic -7, epigeal - 7, epilytic-10 and one species indiffent were grouped into species. Due to meeting frequencies, Cladonia rangiferina was identified as the dominant species in pine forest biomes, and Parmelia vagans in mountain hills, on the contrary, if it was known that the species with low meeting frequencies was Physcia leptalea, which grew in forest biomes, and Parmelia sulcata species in mountain hills were attributed. Through the use of a raster electron microscope, the ways of reproduction of lichens (apothecium, perithecium, soridium, isidium) were determined. Below is an example of a scanner photo of a rare, epileptic lichen species of the Lecanoraceae family - Lecanora allophana The period of formation of ellipse-shaped spores. Among the most common species of lichen in the different biomes studied are as a bioindicator in solving environmental problems by quantitative indicators (Cladonia, Peltigera, Hypogymnia), in obtaining natural coloring (Caloplaca, Lecanora, Acarospora ) and in pharmacology medicinal plants (Parmellia, Cetraria, Peltigera). It is necessary to consider the possibilities of studying the ways of using species belonging to the genera mentioned as Cladonia. In conclusion, the biodiversity of lichens reflects not only their ecological significance, but also their biomedical potential. These studies require further comprehensive study of lichens in Kazakhstan and show that they have a high potential for widespread use in the field of biotechnology and pharmaceuticals. Key words: Lichen, Semey pine forest, small mountain hills of the East. References: Zhumaniyazova A.Zh., Silybayeva B.M., Bukabayeva Zh.T., Kunanbayeva N.S., Anuarbekova A.N. (2025) Semeydin Karagayli ormaninda osetin kinalardin taksonomialyk birlikterin zertteu. Al-Farabi KazUU (Experimental biology), Biologia seriasy, 103. №2 https://doi.org/10.26577/bb202510322 Bukabayeva Zh.T, Abyev S., Silybayeva B.M., Asanova U, Sharipkhanova A.S., Sagdatkyzy (2023) Epiphytic and epigeal lichens bioindicators of air pollution in the Burabay National Park, Kazakhstan. BIODIVERSITAS. Journal of Biological Diversity, vol. 24, pp. 2702-2709. https://doi.org/10.13057/biodiv/d240523 Anderson J, Levesque N, Caron F, Beckett P, Spiers G.A. (2022) A review on the use of lichens as a biomonitoring tool for environmental Journal of Environmental Radioactivity, vol. 243, p. 106797 https://www.sciencedirect.com/science/article/abs/pii/S0265931X21002691 Andreeva E.I. (1978) Flora Sporovykh rastenii Kazakhstana. Lishayniki [Flora of spore plants of Kazakhstan. Lichens] Akademia nauk Kazakhskoy SSR, Almaty, 1978. David L. Hawksworth. (2024) 2024 Mycological book news. Fungal Biology Reviews, vol. 50, p. 100399 https://www.sciencedirect.com/science/article/abs/pii/S1749461324000447 Jessica Allen, James C.Lendemer. (2022) A call to reconceptualize lichen symbioses. Trends Ecology and Evolution, vol. 37, pp. 582-589https://www.sciencedirect.com/science/article/abs/pii/S016953472200057X Jesse D. Miller, John Villella , Daphne Stone , Amanda Hardman. (2020) Using lichen communities as indicators of forest stand age and conservation value. Forest Ecology and Management, vol. 475, p.118436. https://www.sciencedirect.com/science/article/abs/pii/S0378112720312056